Representasi Hiperrealitas dalam Film Not Okay - Affandi, Alfian (Jurnal Ilmiah Wahana Pendidikan, 2024)
The film entitled Not Okay is a film produced by Searchlight Picture which will be released on digital platforms such as Hulu and Disney+ in July 2022. This film, directed by Quinn Shephard, features Danni who lied to all of America by claiming to be a survivor of the Paris bombings. Implicitly, this film also projects the concept of hyperreality which is packaged according to how people live in general. This research focuses on describing how hyperreality is packaged in the film Not Okay. The method used is descriptive qualitative with John Fiske's semiotic approach. The results of the research were that several scenes were found that were related to the four phases of hyperreality, namely the image corresponds to reality, the image distorts reality, the image eliminates reality, and the image is detached from reality. The occurrence of this hyperreality is also influenced by several factors, namely differences in expectations regarding self-concept and the original situation, class differences, and the capitalist system.